2014
DOI: 10.1007/s40653-014-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Community Violence: Loss and Traumatic Grief in African American Elementary School Children

Abstract: The current study examined loss and childhood traumatic grief (CTG) in a sample of 403 African American school children in grades 6-8. Three out of four of these children reported the death of a close family member or friend, with deaths more than twice as likely to occur from illness and disease as from violence. Almost one-quarter of the children reporting a loss from any source scored in the severe traumatic grief range. After statistically controlling for witnessing violence, victimization and family viole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…For the variable-centered analyses, the first research question explored whether the factor structure of a proposed three-factor model of cross-contextual violence exposure that characterizes violence by type and relationship proximity fit the current data. In line with previous research (Jenkins et al, 2014;Lambert et al, 2012;Mitchell et al, 2015), Hypothesis 1 predicted that higher levels of exposure to violence with victims of closer relationship proximity (e.g., self, friends, and family) and more severe violence types (e.g., weapons and death) would be more strongly related to higher levels of internalizing symptoms than exposure to violence with victims of more distant relationship proximity (e.g., acquaintances). The paucity of research using combinations of proximity and type of violence exposure limited the ability to make specific predictions about interactions between factors.…”
Section: The Current Studysupporting
confidence: 79%
See 2 more Smart Citations
“…For the variable-centered analyses, the first research question explored whether the factor structure of a proposed three-factor model of cross-contextual violence exposure that characterizes violence by type and relationship proximity fit the current data. In line with previous research (Jenkins et al, 2014;Lambert et al, 2012;Mitchell et al, 2015), Hypothesis 1 predicted that higher levels of exposure to violence with victims of closer relationship proximity (e.g., self, friends, and family) and more severe violence types (e.g., weapons and death) would be more strongly related to higher levels of internalizing symptoms than exposure to violence with victims of more distant relationship proximity (e.g., acquaintances). The paucity of research using combinations of proximity and type of violence exposure limited the ability to make specific predictions about interactions between factors.…”
Section: The Current Studysupporting
confidence: 79%
“…Previous theory on developmental psychopathology of child traumatic stress suggests that youth may suppress concerns for themselves and experience intense emotional distress when they believe significant attachment figures are in danger (Pynoos, Steinberg, & Piacentini, 1999). As mentioned previously, traumatic grief and associated mental health symptoms, including anxiety, may follow the sudden loss of a loved one (Jenkins et al, 2014; Melhem et al, 2007), and perhaps anticipation or fear of experiencing such a devastating loss could similarly increase anxiety symptoms. Other research indicates that threats to family and friends may also affect youth expectations for their own safety.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Supplementary Tables 1 and 2 summarize the quantitative and qualitative studies, respectively. About half of the studies were conducted in the United States (Balk, 1990;Cox et al, 2016;Fristad et al, 1993;Harris, 1991;Jenkins et al, 2014;Oosterhoff et al, 2018;Servaty-Seib & Hamilton, 2006;Thyden et al, 2020;Van Eerdewegh et al, 1982, 1985Williams & Aber, 2016;Youngblut et al, 2019). The remaining studies originated from the United Kingdom (Abdelnoor & Hollins, 2004a;Abdelnoor & Hollins, 2004b;Pitman et al, 2018), Norway (Burrell et al, 2020;Steele et al, 2009), Sweden (Berg et al, 2014), Denmark (Høeg et al, 2019), Finland (Prix & Erola, 2017), China/ Tibet (Liu et al, 2019) and South Korea (Khang et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In general, the studies reported negative impacts of bereavement on educational outcomes. Five quantitative studies reported lower academic grades in bereaved children and adolescents (Abdelnoor & Hollins, 2004b;Berg et al, 2014;Jenkins et al, 2014;Oosterhoff et al, 2018;Van Eerdewegh et al, 1982, 1985. Whilst Berg et al (2014) additionally reported a higher risk of academic failure longitudinally, Van Eerdewegh et al (1982;1985) did not find any association between bereavement and grade failure in 13 months after bereavement.…”
Section: Bereavement and Educational Outcomesmentioning
confidence: 99%